Pengaruh Kepemimpinan Transformasional dan Komitmen Terhadap Organizational Citizenship Behavior Pada Guru MAN 2 Kota Kediri - Achmad Rozaki Mustofa; Diana Ambarwati; Lina Saptaria (FEB Universitas Maritim Semarang, 2023)
The purpose of this study was to examine the effect of transformational leadership and commitment on organizational citizenship behavior. This research is a quantitative study with a population of all MAN 2 Kediri City teachers. Saturated samples were used in sampling a total of 87 teachers obtained from questionnaires directly to respondents. Data were analyzed using multiple regression. The results showed that transformational leadership and commitment positively influenced organizational citizenship behavior.